The Impact of Social Media Advertising on Consumers' Purchasing Decisions - Deng, Li (SHS web of conferences, 2025)
With the rapid development and popularity of social media, social media advertising has become an indispensable part of enterprise marketing strategy. This study aims to explore the impact of social media advertising on consumers' purchasing decisions. Through literature review, questionnaire survey and data analysis, this paper in-depth studies the characteristics of social media advertising, consumers' attitudes towards social media advertising and the mechanism of social media advertising's influence on consumer purchasing behavior. The results show that social media advertising can significantly influence consumers' purchasing decisions by enhancing brand awareness, enhancing brand trust and promoting user interaction. In addition, this study also found that factors such as personalized push, content quality and user evaluation of social media advertisements have a significant impact on consumers' purchase intention. Based on the research results, this paper puts forward suggestions for optimizing social media advertising strategies, including improving the relevance and attractiveness of advertising content, strengthening interaction with consumers, and rational use of big data analytics. This study provides theoretical basis and practical guidance for enterprises to formulate effective social media marketing strategies, and also provides a new direction for future related research.